Utopia and uchronia. Reflections on the trajectory of a mining city (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article is the result of an ethnographic observation of the process of change undergone by a labor culture associated to the coal mining and its relationship with the city of Lota, located in the center South of Chile a city that has been constituted as a residential and services center along with the development of the monoindustry, from the second half of the nineteenth century. On one hand, it analyzes how this has shaped an historical subject with labor and class identity considering the working, social and living conditions of the mining workers and the population. This historical subject generates a teleological discourse that leads to a utopianist vision during the service life of the mineral´s exploitation. On the other hand, we analyze how the end of the mining activity in 1997, after the coal mine´s closing, causes the subjects to transform their utopia into uchronia; that is to say, how the aim of the narrative that addressed the actions generates an alternative temporality that has no real time, which reveals the difficulties to reconstruct the biography and memory of a specialized community.
Keywords: Lota; coal; social movement; utopia; uchronia